Pengaruh Perilaku Kepemimpinan dan Motivasi Kerja Kepala Sekolah terhadap Kualitas Mengajar Guru di SMP Negeri Sekecamatan Prabumulih Barat - Ardiansyah Ardiansyah; Tri Widayatsih; Mahasir Mahasir (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the influence of leadership behavior and work motivation of school principals on the quality of teacher teaching. This research was carried out at Public Middle Schools in West Prabumulih District which consists of 2 (two) schools, namely Public Middle School 9 Prabumulih and Public Middle School 4 Prabumulih. The time used to conduct this research is 4 (four) months, namely December 2023 to March 2024. The method used in this research is a quantitative approach. The population in this study was 116 people consisting of teachers, school principals, and community leaders. After calculating using the Slovin formula, the number of samples in this study was 90 people. Data collection techniques in this research are questionnaires, observation, and documentation. Instrument testing uses validity and reliability tests. Test the analysis prerequisites using the Normality Test, Homogeneity Test, and Linearity Test. Data analysis uses an Inferential Statistical Test, Multiple Linear Regression, t-test (partial), F-test (simultaneous), and coefficient of determination. The results of this research show that the principal's leadership behavior and work motivation together have a significant effect on the teaching quality of teachers in State Middle Schools in West Prabumulih District. A significance value of 0.00 was obtained, which means it is smaller than 0.05. The influence of all independent variables on the quality of teacher teaching is 92.2% and the remaining 7.8% is influenced by other variables not examined in this research. The conclusion is that the principal's leadership behavior and work motivation influence the quality of teacher teaching. Keywords: Leadership Behavior; Teaching Quality; Work motivation